Peran Bahasa Indonesia Dalam Pembangunan Bangsa - Raja Songkup Pratama; Fariz Aditya; Victoria Grace Daely; Ika Febriana (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
This research discusses the role of the Indonesian language in supporting Indonesia's national development and the challenges faced in preserving and developing it in the era of globalization and modernization. The study employs a literature review approach to analyze the role of the Indonesian language in nation-building. The formulation of the problem includes the role of the Indonesian language in nation-building, challenges in preserving and developing this role, and strategies to strengthen the role of the Indonesian language in the digital era. The results indicate that the Indonesian language plays a crucial role in unifying the nation and enhancing national development. However, challenges such as globalization and modernization pose threats to the purity and sustainability of the Indonesian language. Therefore, increasing understanding and affection for the Indonesian language among the public need to be enhanced through formal education and the development of strategies that adapt to technological advancements and the times.